Organizational Configurations and Performance: A Comparison of Theoretical Approaches - Ketchen, David J.; Thomas, James B.; Snow, Charles C. (Academy of Management Journal, 1993)
Two major approaches to examining the relationship between organizational configurations and performance are found in the strategic management literature. The first, rooted in the concept of strategic groups, is inductive and focuses on a posteriori examinations of industry-specific configurations and their relative performance. The second, a deductive approach, focuses on theory-based predictions. We compared the two approaches using a single set of organizations. The two approaches generated different configurations to describe the hospital industry. The deductively defined configurations explained performance better than the inductively defined configurations, and the deductive approach allowed prediction of the performance differences among configurations. We draw theoretical and methodological implications for future research.